IN-VITRO evidence for the protective properties of the main components of the Mediterranean diet against colorectal cancer: A systematic review. (September 2015) - Rotelli, M.T.; Bocale, D.; De Fazio, M.; Ancona, P.; Scalera, I.; Memeo, R.; Travaglio, E.; Zbar, A.P.; Altomare, D.F.
Abstract Aim Epidemiological studies have shown that the incidence and mortality rates of colorectal cancer (CRC) vary over 10-fold worldwide where within Westernized societies lower rates are observed amongst populations living within the Mediterranean basin, suggesting a significant influence of environment and dietary style in CRC carcinogenesis. Interpretation of the data concerning the benefits of mediterranean (MD) diet is difficult in vivo because of the variability of alimentary regimens used, the differing compliance with dietary supplementation and because of the non-uniform duration of patient cohort observation. Therefore, the aim of this review is to evaluate the in-vitro effects on colorectal cancer cell lines. Methods the literature concerning the in-vitro effects of 4 of the principal components symbolizing the MD such as olive oil (polyphenol), red chili (capsaicin), tomato (lycopene) and red grapes (resveratrol) have been systematically reviewed. Results Several studies have demonstrated that polyphenols form olive oil, lycopene, resveratrol and capsaicin have multiple anticancer properties affecting several metabolic pathways involved in cancerogenesis, apoptosis, and metastasis in CRC cell lines. Conclusion This review summarizes some of the most recent data potentially supportive of the use of MD in CRC chemoprevention, analyzing the in vitro effects of individual components of the MD on CRC cell development, progression, metastasis and apoptosis.